Students’ Acceptance on Blended Learning: A Case Study - Ramadan Ab Hamid, Mohd; Hainida Khairul Ikram, Emmy; Sabariah Buhari, Siti; Ahmad Shuhaimi, Farhanah; Md Nor, Norazmir; Nazrina Camalxaman, Siti; Said, Norimah (International Journal of Engineering and Technology, 2018)
Electronic Learning (E-Learning) has been widely used as a complement to the traditional learning method. It includes the introduction of blended learning (BL) that fully utilises the use of Learning Management System (LMS). The aim of this study is to examine students’ acceptance of blended learning specifically with the use of Openlearning (OL) as an online learning platform to complement traditional teaching. 137 students had participated in this study. OL was introduced to the Health Sciences students, who enrolled in the Principles of Nutrition course. Students explored teaching materials, videos, activities, and several assessments in OL while facilitated by facilitators for 14 weeks. A self-administered questionnaire was given via online to the participants to evaluate their attitudes and acceptance towards OL. Descriptive statistic was used to describe the demographic data and t-test was performed to report the level of acceptance. Overall results showed students were very satisfied with blended learning using OpenLearning as a web-based tool. Students accepted OL as it is easy to use and convenient. They also agreed that the usage of OL in teaching and learning will improve their academic performance. In conclusion, it is proven that Health Sciences students accepted the use of OL in blended learning.